Reformulation of Annual Patent Fee Payment Regulations as an Effort to Prevent the Loss of Intellectual Property Rights: Reformulasi Pengaturan Pembayaran Biaya Tahunan Paten sebagai Upaya Mencegah Hapusnya Hak Kekayaan Intelektual - Olivia Medianna; Gunardi Lie (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Patent protection plays a vital role in supporting technological innovation and economic development. Specific Background In Indonesia, the obligation to pay annual patent fees as mandated by Law No. 13/2016 and Law No. 65/2024 aims to ensure administrative order, yet in practice creates financial barriers for individual inventors, universities, and small enterprises. Knowledge Gap Existing policies do not fully resolve issues of accumulated arrears under earlier regulations and have not provided mechanisms that ensure fair treatment for patent holders with limited financial resources. Aim This study analyzes the urgency of reformulating annual patent fee regulations to prevent the loss of patent rights caused by delays in payment. Results Findings show that regulatory weaknesses, insufficient monitoring systems, and financial limitations among patent holders contribute to high patent deletion rates and low commercialization of research outcomes. Novelty This research proposes a new policy model including progressive fee structures, early warning systems, reinstatement opportunities, creation of a national patent support fund, and digital management through a Patent Information Management System. Implications These reforms are expected to build a more equitable and inclusive intellectual property governance framework that strengthens innovation-driven economic growth in Indonesia. Highlights: High annual fees cause loss of patent rights among financially limited holders. Policy reform is needed to improve fairness and administrative effectiveness. Proposed solutions include progressive fees, early warnings, and system digitalization. Keywords: Patent Policy, Annual Fees, Legal Reform, Innovation Governance